Using the CIRC (Cooperative Integrated Reading and Composition) Model to Improve Vocabulary Mastery and Reading Comprehension - Syafei, Isop; Suaidah, Ai; Mukarom, Mukarom (UIN Sunan Gunung Djati Bandung, 2024)
The Learning Model is a very important component in planning and delivering learning. Learning models have many varieties, one of which is the cooperative model. CIRC (Cooperative Integrated Reading and Composition) type. This study aims to determine the extent to which the CIRC (Cooperative Integrated Reading and Composition) learning model improves vocabulary mastery and reading comprehension of students at Madrasah Tsanawiyah Harapan Baru Ciamis in Arabic language subjects on qirÄ'ah material. The method used in this study is an experimental method with a quasi-experimental design of the pre-test and post-test type. Data collection techniques in this study were observation, interviews, tests, literature studies, and documentation. The sampling in this study was class IX-A and IX-B at MTs. Harapan Baru Ciamis totaling 47 students. The results showed increased students' learning outcomes in vocabulary mastery and reading comprehension at Madrasah Tsanawiyah Harapan Baru Ciamis in the control and experimental class students. This is indicated by the average initial value of vocabulary mastery in the control class of 50.63 to 67.92. While in the experimental class, the initial average score was 53.91 to 76.74. The increase in students' reading comprehension in the control class got an initial average score of 66.71 to 79.42. The average initial reading comprehension in the experimental class was 67.04 to 86.22. The effectiveness of increasing vocabulary mastery with the Jigsaw model in the control class increased by 35.75%, including the ineffective category. The increase in vocabulary mastery in the experimental class using the CIRC model was 49.75%. This shows that increasing vocabulary mastery is included in the less effective category. The effectiveness of increasing reading comprehension in the control class using the jigsaw model was 36.90%, indicating that the model used was included in the ineffective category. While the increase in reading comprehension using the CIRC model was 56.51%. This shows that increasing reading comprehension using the CIRC model is effective.